2011
DOI: 10.1097/hjh.0b013e3283410390
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant of the NEDD4L gene is associated with beneficial treatment response with β-blockers and diuretics in hypertensive patients

Abstract: The functional NEDD4L rs4149601 polymorphism influences the efficacy of β-blocker and/or diuretic-based antihypertensive treatment both in terms of blood pressure reduction and cardiovascular disease protection, whereas diltiazem-based antihypertensive treatment efficacy is not influenced by this NEDD4L polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 31 publications
3
68
0
Order By: Relevance
“…Variants of the NEDD4L gene may also contribute to individual variations in blood pressure 48) and to the outcome of treatment. For example, Svensson-Färbom, et al 49) showed that polymorphism in the NED-D4L gene (rs4149601) influences the efficacy of β-blockerand/or diuretic-based antihypertensive treatment but not diltiazem-based antihypertensive treatment. If the changes in the regulation of these two signaling components would be correlated with treatment efficacy in patients with heart failure (which requires further studies), they might become a genetic and genomic marker of kidney failure in AHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Variants of the NEDD4L gene may also contribute to individual variations in blood pressure 48) and to the outcome of treatment. For example, Svensson-Färbom, et al 49) showed that polymorphism in the NED-D4L gene (rs4149601) influences the efficacy of β-blockerand/or diuretic-based antihypertensive treatment but not diltiazem-based antihypertensive treatment. If the changes in the regulation of these two signaling components would be correlated with treatment efficacy in patients with heart failure (which requires further studies), they might become a genetic and genomic marker of kidney failure in AHF patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Nordic Diltiazem Study (NORDIL), the G allele of rs4149601 was a predictor of thiazide and atenolol response over diltiazem response without consideration of other loci 72 . In contrast, it was the A allele of rs4149601 that was found to predict thiazide responsiveness in a case-control study of hypertensive Chinese subjects 73 .…”
Section: Candidate Variants Contributing To Sodium Reabsorptionmentioning
confidence: 99%
“…The Nordic Diltiazem (NORDIL) study first showed that the blood pressure lowering effects of combination thiazide/β-blocker treatment were greater in carriers of the G allele compared to carriers of the AA genotype (reduction in systolic blood pressure [SBP] of 19.5 ± 16.8 mmHg versus 15.0 ± 19.3 mmHg; P <0.001 and reduction in diastolic blood pressure [DBP] of 15.4 ± 8.3 versus 14.1 ± 8.4 mmHg; P = 0.02 for carriers of the G allele and AA alleles, respectively). By contrast, no difference in response to the calcium channel blocker diltiazem was observed by NEDD4L genotype 39 . The Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) study then showed greater blood pressure lowering in patients with the G allele in response to hydrochlorothiazide but no difference by genotype in response to the β-blocker atenolol 40 .…”
Section: Hypertension Pharmacogenomicsmentioning
confidence: 73%